The effect of premenstrual symptoms on activities of daily life - Dennerstein, Lorraine; Lehert, Philippe; Bäckström, Torbjörn Carl; Heinemann, Klaas (Fertility and sterility, 2010)
To assess impact of premenstrual symptoms on activities of women's daily lives (ADL). Cross-sectional population-based survey. Market research company. A total of 4,085 women aged 14-50 years recruited by random telephone digit dialing in France, Germany, Hungary, Italy, Spain, the United Kingdom, Brazil, and Mexico. None. A telephone interview checklist of 23 premenstrual symptoms, sociodemographic and lifestyle variables, and ADL effects (global question and seven areas). Stepwise regression measured the effect of premenstrual symptoms and sociodemographic factors on ADL. Symptoms and symptom domains (physical and mental) had similar negative effects on ADL. Activities of daily life were predominantly affected by symptom severity. Income level, age, and country also significantly affected ADL. In all, 2,638 women (64.6%) were minimally affected in ADL, 981 (24%) were moderately affected, and 454 (11.1%) were severely affected. Both physical and mental premenstrual symptoms have significant impact on quality of life, assessed as ADL. Up to 35% of women of reproductive age in Europe and Latin America were moderately or severely affected in ADL by cyclical premenstrual symptoms.